Creatures of Habit? What Translators Usually Do with Words - Kenny, Dorothy (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis paper focuses on some of the methodological and theoretical challenges presented by the investigation of "sanitisation" in translated texts through the analysis of semantic pros- ody. The main hypothesis is that target texts tend to use toned down vocabulary compared with their sources, and that this results in the creation of a "sanitised version of the original."